The fame as a passport to the attention: reflections on the use of celebrities in the communication of global marketing - Josmar Andrade (Internext: Revista Eletrônica de Negócios Internacionais, 2008)
The main objective of the present essay is to explore the theme of the use of celebrities in marketing communications, with specific focus in the reception of messages of international standardized campaigns in local contexts. The difficulty to obtain the consumers’ attention is an important reason for the use of celebrities in marketing communication programs, strategy normally used to increase the attention levels and, as an effect of great importance, to transfer attributes associates to these personalities to brands, announced offers and companies. Offering subsidies to this discussion, the present work carries through literature revision enclosing and correlating the aspects of celebrities endorsement in marketing, attention allocation, the culture and the identity as references for elaborating marketing communication strategies. To its end, theoretical models are presented, integrating the diverse aspects of the quarrel and pointing to questions that deserve greater deepening of the academic research and that impact the practitioner world.